2007
DOI: 10.1152/physiolgenomics.00188.2006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves the net balance of cardiac Ca2+ handling protein expression in heart failure

Abstract: The molecular basis of the beneficial effects associated with exercise training (ET) on overall ventricular function (VF) in heart failure (HF) remains unclear. We investigated potential Ca(2+) handling abnormalities and whether ET would improve VF of mice lacking alpha(2A)- and alpha(2C)-adrenoceptors (alpha(2A)/alpha(2C)ARKO) that have sympathetic hyperactivity-induced HF. A cohort of male wild-type (WT) and congenic alpha(2A)/alpha(2C)ARKO mice in a C57BL/J genetic background (5-7 mo of age) was randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
1
38

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 41 publications
(43 reference statements)
15
102
1
38
Order By: Relevance
“…At 7 months of age, when α 2A /α 2C ARKO mice display severe HF, exercise training restored cardiac NCX expression levels, and increased SERCA2, and phosphorylated phospholamban expression levels at both residues Ser 16 and Thr 17 , which resulted in improved left ventricular function. These findings suggest that the improvement in intracellular Ca 2+ regulation is a molecular mechanism underlying the benefits of exercise training for overall ventricular function in severe HF (18).…”
Section: Impact Of Exercise Training On Cardiac Functionmentioning
confidence: 77%
See 4 more Smart Citations
“…At 7 months of age, when α 2A /α 2C ARKO mice display severe HF, exercise training restored cardiac NCX expression levels, and increased SERCA2, and phosphorylated phospholamban expression levels at both residues Ser 16 and Thr 17 , which resulted in improved left ventricular function. These findings suggest that the improvement in intracellular Ca 2+ regulation is a molecular mechanism underlying the benefits of exercise training for overall ventricular function in severe HF (18).…”
Section: Impact Of Exercise Training On Cardiac Functionmentioning
confidence: 77%
“…In this context, we have suggested that exercise training would improve cardiac function in HF animals by, changing, at least in part, the expression of proteins involved in cardiac Ca 2+ homeostasis. We found that exercise training significantly increased fractional shortening toward normal levels and improved the net balance of cardiac Ca 2+ proteins involved in Ca 2+ transsarcolemmal flux and sarcoplasmic reticulum Ca 2+ reuptake in a genetic model of sympathetic hyperactivity-induced HF based on α 2A and α 2C adrenoceptor gene inactivation in mice (α 2A / α 2C ARKO) (18). At 7 months of age, when α 2A /α 2C ARKO mice display severe HF, exercise training restored cardiac NCX expression levels, and increased SERCA2, and phosphorylated phospholamban expression levels at both residues Ser 16 and Thr 17 , which resulted in improved left ventricular function.…”
Section: Impact Of Exercise Training On Cardiac Functionmentioning
confidence: 93%
See 3 more Smart Citations